Influence of compensation and burnout on performance at the Papua Province Central Statistics Agency - Suyoto, Suyoto; Hidayah, Zainur; Maharani, Anita (Privietlab, 2024)
Often organizations make compensation the only main variable in pursuing employee performance targets, but they forget about excessive workloads that cause burnout to employees. Our study aims to test and analyze the effect of compensation and burnout on employee performance at the Central Bureau of Statistics of Papua Province. The analysis used by the researcher is a multiple regression model analysis technique, namely, to predict how compensation and burnout affect employee performance at the Papua Province Central Statistics Agency, by connecting compensation variables (X1) and burnout (X2) to performance variables (Y). The research instrument was tested using Validity and Reliability Tests. This study found that compensation influenced performance, while Burnout was not proven to influence performance. From this study we have provided empirical findings in the use of burnout variables in influencing employee performance. These findings are interesting because research is still rarely conducted in Papua, and this is the first-time research has been conducted with the Burnout variable in the BPS work unit of Papua Province.